UTILIZATION OF SILICA NANOFLUID FOR VEHICLE RADIATOR COOLING SYSTEM - Surono, Arif; Trisna Dewi , Aptika Oktaviana (LPPM Universitas Duta Bangsa Surakarta, 2023)
This research investigates the effect of a silica (SiO2) nanofluid flow system on the radiator performance function. The initial preparation is to take SEM photos to find out the microstructure. Next, mix the silica nanoparticles with water using a variation of 0.1%, 0.3%, and 0.5%, using a magnetic stirrer, to disperse the mixture, an ultrasound device is used. The liquid that has been separated from the sediment is tested using a series of test equipment consisting of a radiator, flow meter, pump, heater, water tank, and term reader. Data taken is the temperature of the liquid entering and leaving the radiator and the walls entering and leaving the radiator. This research uses 3 variations of fluid flow velocity, namely 2.5, 4.5, and 6 LPM. The result is a decrease in temperature at a fluid flow rate of 6 LPM which is able to release heat to the environment properly. The temperature drop that occurred was 2.5%. then the lowest average radiator effectiveness value at the lowest speed of 6 LPM is 0.905, the highest is at a fluid flow rate of 4.5 of 0.930.